TANTANGAN DAN PROSPEK IMPLEMENTASI E-GOVERMENT DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI ERA DIGITAL - Yefry Kapitan; Kadek Dedy Suryana; Kadek Mery Herawati (Yayasan Nusantara Hasana Berdikari, 2024)
The purpose of this research is to determine the process of challenges and prospects for implementing E-government in improving the quality of public services, as well as the inhibiting factors in implementing E-government in improving the quality of public services in the Legal Digital Era. The method used in preparing this research is a normative approach which is supported by empirical where this research approach uses a statutory approach and a Legal Concept Analysis approach. Where the nature of the research uses exploratory (exploratory) research. The results of this research are the elements of successful implementation of e-government through pro applications, which are assessed as good, namely the Capacity Element (resources) in Denpasar City Dukcapil, with the availability of human resources, namely operators who have been equipped with knowledge and skills from training conducted by the Department. Denpasar City Population and Civil Registration. Elements that have not been implemented well by the Denpasar City Dukcapil are; a. Support element, because seen from the willingness of the people of Denpasar City who still lack awareness of the importance of electronic-based service systems as evidenced by the lack of people accessing the Pro application, many people even stated that they were not aware of the existence of the Pro application; b. Value element (benefits) because some people have not felt the benefits of the Pro Application because after they have provided services using the Pro application in processing documents but are still told to come back to the office to complete the data. Inhibiting factors in implementing e-government through the pro application at the Denpasar City Dukcapil are; a. unstable network; b. People do not understand technology; c. Server error/full; d. People's mindset.